Identification and characterization of yeast SNF1 kinase homologs in Leishmania major - Shoeran, Gaurav; Anand, Namrata; Kaur, Upninder; Goyal, Kapil; Sehgal, Rakesh (Frontiers in Molecular Biosciences, 2025)
BackgroundSucrose Non Fermenting1 (SNF1) constitutes a family of protein kinases conserved in eukaryotes, plants, and fungi. SNF1 has been known to play a crucial role in stress adaptation and metabolism, enabling organisms to respond to changing environmental conditions. Initially identified in yeast, SNF1 is essential for shifting from the primary carbon source, glucose, to secondary carbon sources like sucrose. Homologs of this protein family were identified in Leishmania major, a protozoan parasite and we aimed to determine their role in this parasite.MethodsIn the present study, we identified the putative homologs of SNF1 kinase in L. major and knock out strains were prepared using the CRISPR-Cas9 knock-out strategy. The developed strains were evaluated for their growth, characteristics, protein expression and ultra structural changes in vitro and virulence in a mouse model.ResultsOne of the strain named N2, was found to be completely avirulent and showed limited growth, lack of glycosomes and had a fewer mitochondria with deformed cristae. The N2 strain failed to produce infection in mice when compared to WT mice. Proteome analysis revealed an increase in ribosomal proteins in the N2 strain, highlighting the role of ribosomes in stress adaptation.ConclusionThe essentiality of this gene for developing infections in mice underscores its potential in the development of future antileishmanial therapies and live attenuated strains.